2001
DOI: 10.1034/j.1600-079x.2001.300308.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of fetal size and length of gestation on 6‐sulphatoxymelatonin excretion in adult life

Abstract: Recent studies have shown that intrauterine growth retardation or fetal distress in human infants is associated with a pronounced reduction in melatonin secretion during the first 3 months of life. It is not known whether these associations persist beyond infancy. We have therefore examined the relationship between birthsize and melatonin secretion in 159 men and women aged 20, born in Adelaide, South Australia. Melatonin secretion was estimated by analysing the overnight urinary excretion of 6-sulphatoxymelat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 24 publications
1
24
1
Order By: Relevance
“…13 Although human data are scarce, studies suggest that FGR may alter the maturation of sleep circadian rhythms in neonatal life and based on actigraphy data, sleep efficiency (SE) later in life. 14 Compounding these sleep disturbances, being born preterm, whether the infant is growth restricted or not, is associated with altered maturation of sleep in infancy. 15 This is of particular concern, as sleep is the main behavioral state during the neonatal period and is known to be important for neurological development.…”
Section: Introductionmentioning
confidence: 99%
“…13 Although human data are scarce, studies suggest that FGR may alter the maturation of sleep circadian rhythms in neonatal life and based on actigraphy data, sleep efficiency (SE) later in life. 14 Compounding these sleep disturbances, being born preterm, whether the infant is growth restricted or not, is associated with altered maturation of sleep in infancy. 15 This is of particular concern, as sleep is the main behavioral state during the neonatal period and is known to be important for neurological development.…”
Section: Introductionmentioning
confidence: 99%
“…The comparison between the children studied here and the young adults studied by Kennaway et al [4]relies on the stability of melatonin production within this period of life. Waldhauser et al [11]have taken a single blood sample around midnight from 367 persons at the age of 3 days up to 90 years and shown that melatonin levels are at maximum at the age of 1–3 years and decrease then by about 80 % until the age of 15–20 years.…”
Section: Discussionmentioning
confidence: 99%
“…Kennaway et al [4]assumed that prenatal events determine the great inter-individual variability of melatonin production even in adults. To verify this they related overnight urinary excretion of aMT.6S from 159 young adults (20 years) to actual body size (height, weight, BMI) and to gestational age and body size at birth (height, weight, PI).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future studies should examine seasonal fluctuations in maternal weight gain in order to explore these factors. There is also evidence suggesting that the maternal environment may influence the dprogrammingT of the fetal suprachiasmatic nucleus, which is involved in the generation of circadian rhythms [36,37]. Because of the links between melatonin, growth hormone and bone remodelling [38], these mechanisms require further scrutiny.…”
Section: Does Prenatal Vitamin D Alter Fetal Development?mentioning
confidence: 99%